Source Identification Problem for a Parabolic Equation with Multipoint Nonlocal Boundary Condition. (5th August 2020) - Ashyralyyev, Charyyar; Akkan, Pinar
Abstract: We study a source identification problem for a parabolic equation with multipoint nonlocal boundary condition. Stability estimates for the solution of abstract source identification problem are established. In application, stability estimates for the solution of the overdetermined mixed boundary value problem for multidimensional parabolic equation are obtained. The first and second order of accuracy difference schemes for the approximate solution of this problem are constructed. Stability estimates for solutions of these difference schemes are proved. Numerical illustration for a simple test problem is presented.